Perancangan Sistem Informasi Pada SMA 15 Muhammadiyah Jakarta Berbasis Web Menggunakan Metodel Agile Scrum - Fikri Husein; Faiz Errabani Alfaqih; Bibit Sudarsono; Andreyestha Andreyestha (Bianglala Informatika, 2026)
The New Student Admission (PPDB) process at SMA Muhammadiyah 15 Jakarta has traditionally relied on paper forms and manual verification. This method created several issues, including slow administration, a high risk of data entry errors, limited accessibility for applicants outside Jakarta, and a lack of transparency in monitoring registration status. This study aims to design and develop a web-based information system integrated with PPDB forms to provide a more efficient, accurate, and accessible registration process. The system is expected to accelerate administrative workflows and ensure transparency in the selection process. The development method applied is Agile Scrum, a software framework emphasizing short iterations (Sprints), team collaboration, and adaptability to evolving requirements. The stages involved needs analysis, Backlog preparation, sprint Planning, system design and implementation, blackbox testing, and evaluation based on user feedback. The results indicate that the developed system successfully addresses administrative inefficiencies, reduces data entry errors, and provides essential features such as digital document uploads, automated validation, and an administrative dashboard. Consequently, the system improves transparency, accountability, and effectiveness in the PPDB process.